Community Participation in Enhancing the Tourism Appeal of Pajamben Valley in Binangun Village, Pataruman District, Banjar City - Dikri Praditya Maulana Ganar; Neti Sunarti; Arie Budiawan (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study was motivated by the suboptimal level of community participation in enhancing the attractiveness of Lembah Pajamben Tourism in Binangun Village, Pataruman District, Banjar City. This issue is reflected in the limited involvement of local residents in decision-making processes, the implementation of tourism management activities, and the utilization of tourism development outcomes. The study aimed to examine how community participation contributes to improving the attractiveness of Lembah Pajamben Tourism in Binangun Village, Pataruman District, Banjar City. A descriptive qualitative research method was employed. The study involved six informants selected through purposive sampling, consisting of the Village Head, a member of the Village Consultative Body (BPD), a community leader, a youth leader, a local entrepreneur, and a tourist. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings indicate that community participation in enhancing the attractiveness of Lembah Pajamben Tourism has been implemented but remains suboptimal. In the decision-making aspect, community members have begun participating through deliberation meetings and by providing suggestions; however, their involvement is still limited. Regarding the implementation of activities, community members have participated in mutual cooperation (gotong royong), maintaining cleanliness, improving the surrounding environment, and contributing labor and ideas to tourism development, although the level of participation has not been evenly distributed. In terms of the utilization of development outcomes, the community has benefited economically through business activities and micro, small, and medium enterprises (MSMEs) while also contributing to the maintenance of tourism facilities. Nevertheless, challenges remain, including the low level of awareness among some residents and visitors in preserving tourism facilities, as well as limited resource support. In conclusion, community participation is a crucial factor in enhancing the attractiveness of Lembah Pajamben Tourism. Therefore, broader community involvement should be encouraged through strengthened communication, community empowerment initiatives, and improved collaboration among the village government, tourism managers, and local residents to ensure the sustainable development of the tourism destination. Keywords: Community participation, tourism attraction, tourism development, Lembah Pajamben.